Sugarcane productivity with waste water application from the sucroenergetic industry (Research, Society and Development, 2020)
To fertirrigation with residual water as to vinasse it can be a viable alternative for nutrition and water supply for Sugarcane. In this sense, or present study as objective, a descriptive analysis on the production of the Sugarcane during 5 harvests in the function of the application of vinasse in a non-Southwest Goiano energy industry. There were pigtails given from the productivity of forty plots different cultivated with sugar cane for 5 years (crops 14/15; 15/16; 16/17; 17/18; 18/19), in each crop were selected four areas with 2nd crops; 3rd; 4th and 5th in the condition of drying and fertigation with vinasse. You are given were analyzed by means of descriptive statistic in the electronic spreadsheet (Excel) with a reliability level of 95%, it was calculated on the average for the cuts and the subsequent calculation or deviation pattern, the were results presented in tables and figures. Comparing the fertirrigated areas with vinasse and dryland, the fertirrigated areas will present higher average producís to the dryland in 7.51; 12.48; 15.29 and 16.43% for the 2nd, 3rd, 4th and 5th cut, respectively. Fertigation with vinasse promotes productivity increases for the 2nd, 3rd, 4th and 5th cut in relation to the rainfed condition. To sugar cane. The vinasse used via fertigation is recommended to suppress the hydric and nutrient needs, it is essential not to grow sugarcane.